Demographic factors influencing job burnout among academic staff in private universities in Kwara state: implication for human resource management in Nigeria / Lasisi, Adekola Kamil - Lasisi, Adekola Kamil (2022)
Demographic factors influencing job burnout among academic staff in private universities in Kwara State was investigated. Descriptive research method was used and one hundred purposively selected academics from the two private universities in Kwara State were the participants of this study. Four null hypotheses were tested at 0.05 critical region. Oldenburg Burnout Inventory (r = 0.82 and 0.83) was used. The findings indicated that there were significant differences in the job burnout of the participants on the bases of gender, age, marital status and academic qualifications. Recommendations, as well as the implication of the findings for human resource management were highlighted.